Distribution and off–shelf transport of dissolved manganese in the East China Sea - Wang, Zhaowei; Ren, Jingling; Xuan, Jiliang; Liu, Sumei; Zhang, Jing (Frontiers in Marine Science, 2023)
To gain a better understanding of the geochemical behavior of dissolved manganese (Mn) in the marginal seas with respect to distribution and exchange fluxes, more than 200 water samples were collected in the East China Sea (ECS) in May, August, and October of 2013. The concentration of dissolved Mn in the ECS ranged from 1.1 to 81.5 nM, with a gradual decrease with distance from the shore. Seasonal distribution of dissolved Mn varies significantly in the Changjiang estuary, mainly regulated by freshwater input from the Changjiang (Yangtze River) and redox variations. The ECS continental shelf is an important source of Mn for adjacent waters, and the export of Mn–rich coastal waters had an important effect on its re-distribution and internal cycling. The dynamic variation fluxes of water and dissolved Mn across the 100– and 200–m isobaths in the ECS were calculated with an aid of the Finite-Volume Coastal Ocean Model (FVCOM). The ECS continental shelf exported (5.69 ± 1.14) × 108 mol/yr of Mn into the East/Japan Sea from the Tsushima Strait. The Kuroshio surface waters receive an additional (1.02 ± 3.12) × 108 mol/yr of Mn from the ECS continental shelf through a cross–shelf exchange process, which could potentially affect dissolved Mn in the Northwest Pacific. Our data suggest that off-shelf transport from the ECS continental shelf is essential for understanding the biogeochemical cycles of trace metals in the Northwest Pacific Ocean and the East/Japan Sea.